Increased risk of neurodegenerative dementia in women with migraines: A nested case–control study using a national sample cohort. Issue 7 (February 2019) - Lee, Sang-Yeon; Lim, Jae-Sung; Oh, Dong Jun; Kong, Il Gyu; Choi, Hyo Geun
Abstract : Abstract: The present study aimed to evaluate the association between migraines and dementia. Data were collected from 11, 438 dementia participants who were 1:4 matched by age, sex, income, region of residence, hypertension, diabetes, and dyslipidemia with 45, 752 controls from the Korean National Health Insurance Service-National Sample Cohort from 2002 to 2013. Dementia was diagnosed using the International Classification of Disease-10 (ICD-10) codes (G30 or F00). For the integrity of diagnoses, we included only participants ≥60 years old who had been diagnosed with an ICD-10 code twice or more during ambulatory visits for the same episode. For migraine (ICD-10 code, G43), we included participants who had visited outpatient clinics twice or more for the same episode. In both dementia and control groups, a previous history of migraine was investigated. Approximately 7.7% (881/11, 438) of patients in the dementia group and 6.3% (2888/45, 752) of those in the control group had a history of migraine ( P < .001). The crude and adjusted odds ratios (ORs) for migraine with dementia was 1.22 (95% confidence interval [CI] = 1.13–1.32, P < .001) and 1.13 (95% CI = 1.05–1.23, P = .002), respectively. In the subgroup analyses according to age and sex, women demonstrated a significantly higher adjusted OR for migraine with dementia, whereas men did not exhibit an association between migraine and dementia. In a nested case–control study using a national sample cohort, migraine increased the risk of dementia in women. Abstract : Supplemental Digital Content is available in the text